Midterm single-center results after endovascular aneurysm sealing reveal a high rate of stent graft migration, secondary aneurysm ruptures, and device-related reinterventions - Hatzl, Johannes; Peters, Andreas; Pfeiffer, Sabine; Meisenbacher, Katrin; Bischoff, Moritz; Böckler, Dittmar (Journal of vascular surgery, 2021)
Objective - To report procedural results and mid-term follow-up outcomes of patients treated with endovascular aneurysm sealing (EVAS) for abdominal aortic disease. - Methods - In this retrospective observational study, all patients treated with EVAS between March 2013 and January 2018 for abdominal aortic aneurysm (AAA) or abdominal penetrating aortic ulcer were included. The datasets included demographics, aneurysm morphology, and procedural and clinical surveillance outcomes. Furthermore, patients treated within the original instructions for use (IFU-group) were compared with patients treated outside the IFU (non-IFU-group) with regard to survival, reintervention-free survival, freedom from type I endoleak, and freedom from stent graft migration. - Results - Seventy patients were included (67 male; median age, 72.5 years). Sixty-five patients were treated for AAA and 5 patients for abdominal penetrating aortic ulcer. Sixty-nine cases were treated electively (98.6%). Technical success was achieved in 68 cases (97.1%). The median clinical follow-up was 50.5 months (interquartile range, 29.3-62.7 months) with a median computed tomography angiographic follow-up of 38.5 months (interquartile range, 17.1-60.2 months). There were five deaths during the study period (7.1%), four of which were aneurysm related (5.7%). Five secondary AAA ruptures were detected (7.1%). Overall, 25 of 70 patients (35.7%) underwent 35 reinterventions, mostly owing to thrombotic complications (18.6%), stent graft migration (17.1%), and type I endoleak (12.9%). Fifteen patients were treated outside of the IFU (non-IFU-group) (21.4%). The estimated reintervention-free survival for the entire cohort at 30 days and 1, 3, and 5 years was 94.3%, 88.5%, 72%, and 56.9%, respectively. Freedom from stent graft migration at 1, 3, and 5 years was 98.6%, 82.0%, and 47.3%, respectively. The estimated freedom from type I endoleak at 30 days and 1, 3, and 5 years in the IFU-group was 100%, 100%, 94.9% and, 91.1% and significantly different when compared with the non-IFU-group with 79.5%, 72.2%, 72.2%, and 72.2% (P = .012). - Conclusions - Although the technical and initial results were satisfying, the mid-term results were disappointing. The enforcement of a close follow-up protocol for all patients treated with EVAS, especially vigilant for stent graft migration to prevent secondary type I endoleak and rupture, is strongly recommended.